1990
DOI: 10.1002/1097-4679(199005)46:3<306::aid-jclp2270460310>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of two expressed emotion scales with the Camberwell family interview

Abstract: The relationship of the Camberwell Family Interview (CFI) with two self‐report scales purported to measure levels of expressed emotion was assessed. Fifteen schizophrenic patients and 22 of their relatives completed the Level of Expressed Emotion Scale (LEE) and the Influential Relationships Questionnaire (IRQ). The relatives of patients also participated in Camberwell Family Interviews (CFI). Results supported the value of the self‐report measures in evaluating the affective environment of patients with schiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 5 publications
0
48
0
1
Order By: Relevance
“…However, the correlation between the total score on the LEE Relative Version and the number of critical comments relatives made during the CFI was only .38 (Kazarian, Malla, Cole, & Baker, 1990). For the Patient Version of the LEE, total LEE score was correlated .32 with the number of critical comments relatives made during the CFI.…”
Section: Level Of Expressed Emotion Scale (Lee)mentioning
confidence: 89%
See 1 more Smart Citation
“…However, the correlation between the total score on the LEE Relative Version and the number of critical comments relatives made during the CFI was only .38 (Kazarian, Malla, Cole, & Baker, 1990). For the Patient Version of the LEE, total LEE score was correlated .32 with the number of critical comments relatives made during the CFI.…”
Section: Level Of Expressed Emotion Scale (Lee)mentioning
confidence: 89%
“…However, in circumstances that call for a fast estimate of the affective climate in the family, the minimal time cost of a PC assessment appears to be greatly outweighed by its possible benefits as negative prognostic indicator. Mixed predictive validity for schizophrenia (Jarbin et al, 2000;Maron et al, 2002;Thompson et al, 1995) FMSS EOI and overall EE, r ϭ .38 (Magaña et al, 1986) Predicts recovery in depressed children (Asarnow et al, 1993) Predicts relapse of depression but not mania in bipolar patients (Yan et al, 2004) LEE 10-15 min 60-item questionnaire completed by patients or relatives LEE and CFI Criticism, r ϭ .38 for relatives' version; r ϭ .32 for patients' version (Kazarian et al, 1990) Predicts rehospitalization at 2 and 5 years for schizophrenia (Cole & Kazarian, 1993) Predicts rehospitalization in mixed patient sample (Donat, 1996) FAS 5-10 min 30-item questionnaire completed by relatives FAS and overall EE, r ϭ .38 (calculated from Predicts relapse in patients with psychotic disorders (Kavanagh & Pourmand, 2005) PC 1 min One question completed by patients…”
Section: Summary and Recommendationsmentioning
confidence: 99%
“…Proxy measures of EE were obtained using the Infl uential Relationships Questionnaire (IRQ; Kazarian & Baker, 1987), which includes three dimensions of perceived parental style: care, overprotection and criticism. However, these subscales correlate weakly with independent CFI ratings (Kazarian et al, 1990), and the conceptual similarity of the IRQ to the EE construct remains tenuous. Nevertheless, it was reported that parental criticism and overprotection were positively correlated with composite ratings of self-harm, based on yes/no responses to questions about the occurrence of suicidal ideation, planning, threats, suicide attempts and other forms of self-injury.…”
Section: Expressed Emotion and Self-harmmentioning
confidence: 99%
“…Only one study of 15 schizophrenic patients and 22 of their relatives has looked at LEE filled in by patients [25]. The total score on the patient version of the LEE showed a 0.32 correlation with the number of critical comments reported on the CFI critical comments (CFI-CC).…”
Section: Comparison Of Feers With Alternative Studies Of Patient Percmentioning
confidence: 99%